Investigating the impact of relationship quality during an internship on millennials' career decision and gender differences - Heo, Cindy Yoonjoung; Kim, Seongseop (Sam); Kim, Bona (2018)
The hospitality industry has been struggling to attract and retain quality employees. Labor force demographics in the hospitality industry are changing. The first wave of Millennials has started to enter the workforce, and Millennials are the fastest growing segment of said workforce. In addition, the rate of participation of females in today$1 (Bs hospitality workforce is growing. Even though several researchers have studied Millennials as hospitality employees, limited research has explored the importance of the quality of relationships Millennials have with colleagues and customers; in addition, gender differences among Millennials have not been extensively examined. The Commitment-Trust (CT) theory suggests that relationship commitment and trust encourage cooperative behaviors that sustain long-term relationships. This study attempted to investigate whether the relationship quality encountered by Millennials during their internships has an impact on their job satisfaction or career decisions based on commitment-trust theory; in addition, gender differences in relationship quality were examined.s
Keywords: Generation Y